UMA REVISÃO BIBLIOGRÁFICA REFLEXIVA SOBRE A ABORDAGEM DOS RIACHOS DEGRADADOS NA ESCOLA SOB A PERSPECTIVA DAS SITUAÇÕES DE ESTUDO NA EDUCAÇÃO AMBIENTAL - Cavalheiro, Laísa Wociechoski; Nishijima, Toshio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The problem about degraded streams is a matter of citizenship that must pervade the school life.The approach on these questions in the perspective of Environmental Education is a way to moveindividuals in order to develop awareness to preserve water sources. The general objective of thiswork consists in analyzing, under the view of the Environmental Education in the school, theproblem about degraded streams. The specific objectives are: to relate the methodologicalproposal of the Study Situations to the Environmental Education and; reflect about thepreservation of the streams in the perspective of the Environmental Education in the school. Themethodological approach used in this research consists of a bibliographic review in order to gatherinformation, which is systematized, synthesized and reorganized after critical reflection of theauthors, and construct (or reconstruct) ideas by creating a theoretical frame which is able to support or subsidize approaches, in the school, on degraded streams, in the perspective of theEnvironmental Education and the strategy of the Study Situations. The Environmental Education inthe school is a dialogical way for the students to become aware, by means of their individual andcollective experiences, of the importance of the preservation of water sources and the adoption ofmeasures for mitigation of the negative anthropic impact on Brazilian streams, while the StudySituations are an adequate methodology to the sensitization of the individuals because thesesituations work with specific knowledge allied to social matters, contextualizing in this way theteaching proposals to the reality of each single school.